Paediatric dialysis at a tertiary hospital in South-West Nigeria: A 4-year report (2022)
Introduction: Dialysis is potentially lifesaving in children with acute kidney injury (AKI) or chronic kidney disease (CKD), but availability is limited in low-income countries and lower-middle-income countries (LMICs). Methods: In the present study, we perform a 4-year study of patients who received peritoneal dialysis (PD) or haemodialysis (HD) at the Paediatric Nephrology Unit of the University College Hospital Ibadan, Nigeria. Subgroup analysis was performed on patients with sepsis or malaria AKI who underwent HD or PD for predictors of in-hospital mortality. Results: A total of 167 children aged 7 days to 18 years, median 7 (interquartile range 3–12) years, (60.5% males) were studied. In total, 129 (77.2%) had AKI, while 38 had CKD. Regarding AKI, 83 children (64.3%) received HD only, 42 underwent PD only, while 4 underwent both HD and PD. Malaria AKI was treated with HD in 43 (51.8%) or PD in 8 (10.5%), while sepsis AKI was treated with HD in 20 (21.4%) or PD in 33 (78.6%). Mortality in AKI was 16.3% overall, 10.8% in children on HD only, and 26.2% in children on PD only. Patients with sepsis AKI had higher mortality compared to patients with malaria AKI (RR 7.96) [1.70–37.37]). Subgroup analysis showed that age, diagnosis, and dialysis modality were not independent risk factors for mortality. The aetiology of CKD was glomerulonephritis in 26 (68.4%): treatment was HD in 36 and PD in 2 with mortality being 26.3%. Conclusions: PD for AKI showed relatively good outcomes in a LMIC. However, funding and support for a formal dialysis program for the management of AKI and CKD are needed.